On the mass assembly of low-mass galaxies in hydrodynamical simulations of structure formation - de Rossi, Maria Emilia (2013)
A population of galaxies is simulated in a cosmological box in order to analyse generic trends for the stellar, baryonic and halo mass assembly of low-mass galax- ies (M∗ 3 × 1010M⊙) as a function of their present halo mass, in the context of the ΛCDM scenario and common subgrid physics schemes. We obtain that smaller galaxies exhibit higher specific star formation rates and higher gas fractions, specially at low redshifts. Although these trends are in rough agreement with observations, the mean simulated specific star formation rates and gas fractions tend to be lower than observed values since z ∼ 2. The simulated galaxy stellar mass fraction increases with halo mass, consistently with semi-empirical inferences. However, the predicted correlation between them shows negligible variations up to high z, while these infer- ences seem to indicate some evolution. Our results also suggest that the hot gas mass in local halos is higher than the central galaxy mass by a factor of ∼ 1 − 1.5, with this factor increasing up to ∼ 5 − 7 at z ∼ 2 for the smallest galaxies. The average stellar, baryonic and halo evolutionary tracks of simulated galaxies, though with a large scatter, show that smaller galaxies tend to delay their baryonic and stellar mass assembly with respect to the halo one. Therefore, in these simulations, the upsizing trend associated to the halo growth is reverted to a downsizing trend in the case of the stellar and baryonic growth. The Supernova feedback treatment included in this model seems to play a key role on this behaviour albeit the trend is still weaker than the one inferred from observations. Simulated galaxies seem to assemble their stellar mass still too early with respect to observations, being this trend more significant for smaller systems. Finally, at very high redshifts (z > 2), the overall properties of simulated galaxies are not in large disagreement with those derived from observations, at least in the mass range where comparisons can be made.